PENINGKATAN HASIL BELAJAR IPA DENGAN MODEL PEMBELAJARAN DISCOVERY LEARNING BAGI SISWA KELAS IV SDN TINGKIR LOR 2 TAHUN AJARAN 2017/2018 - Hidhayah, Arum Puspa; Slameto, Slameto; Radia, Elvira Hoesein (KALAM CENDEKIA PGSD KEBUMEN, 2018)
AbstractThis study aims to improve the learning outcomes of natural sciences through Discovery Learning model in the fourth grade students on Tingkir Lor 02 Salatiga State Elementary Schools. This type of research is a Classroom Action Research with two cycles. Both cycles consist of three meetings. The subjects of the study were the fourth grade students. The initial condition showed that the score was 62,15 with the total number of students who passed were only 8 students and the number of students who hasn?t passed were 17 students. At the first cycle of natural sciences learning the outcomes increased to become 74. It means the percentage of completeness reached 76%. At the second cycle the average of student?s learning outcomes increased again to become 80,32. Showed that percentage of completeness reached 88%, thus it can be concluded that the Discovery Learning model can improve student learning outcomes.Keywords: Discovery Learning Model, Science Learning Outcomes AbstrakPenelitian ini bertujuan untuk meningkatkan hasil belajar IPA menggunakan model pembelajaran Discovery Learning pada siswa kelas IV di SD Negeri Tingkir Lor 02. Jenis penelitian ini adalah penelitian tindakan kelas dengan dua siklus. Siklus I dan II terdiri dari tiga kali pertemuan. Subjek penelitian adalah siswa kelas IV. Pada kondisi awal nilai rata-rata adalah 66,12 dengan jumlah siswa tuntas sebanyak 8 siswa dan jumlah siswa tidak tuntas sebanyak 17 siswa. Pada siklus I rata-rata hasil belajar IPA meningkat menjadi 74 dan pada siklus II rata-rata hasil belajar siswa meningkat lagi menjadi 80,32. Presentase ketuntasan hasil belajar siswa juga mengalami peningkatan. Pada siklus I presentase ketuntasan mencapai 76% dan pada siklus II presentase ketuntasan mencapai 88%, dengan demikian dapat disimpulkan bahwa model pembelajaran Discovery Learning dapat meningkatkan hasil belajar. Kata kunci: Model Pembelajaran Discovery Learning, Hasil Belajar IPA.